MEMANDANG MUKJIZAT PENYEMBUHAN DALAM TERANG IMAN - Elvin Atmaja Hidayat (Litbang STFT Widya Sasana Malang, 2018)
Since the beginning of its existence, Christianity has been often associated with “paranormal healing”. Jesus himself, with His disciples, often performed healing as a sign of the presence of the Kingdom of God in the world, even in person who was healed. The widespread interest and belief in miracles of physical and spiritual healing, in essence, does not degrade the noble dignity of the Christian faith. On the contrary, this increasingly popular phenomenon can help the Church maintain its existence and re-articulate its relevance for the faithful. More recently, the number of these “miracle healing” groups, both outside and within the Church, is increasingly widespread and likely to obscure faith. Because of this urgency, the Church should seek ways to investigate as deeply as possible the nature of this healing, especially in order to prevent people from being astray. Sejak awal keberadaannya, agama Kristen sering dikaitkan dengan “penyembuhan paranormal”. Yesus sendiri, dengan murid-murid-Nya, sering melakukan penyembuhan sebagai tanda kehadiran Kerajaan Allah di dunia, banyak orang yang disembuhkan. Pada hakekatnya, kepentingan dan keyakinan yang meluas tentang mukjizat penyembuhan fisik dan spiritual, tidak menurunkan martabat mulia iman Kristen. Sebaliknya, fenomena yang semakin populer ini dapat membantu Gereja mempertahankan eksistensinya dan mengartikulasikan relevansinya bagi umat beriman. Baru-baru ini, banyak yang mengalami “mukjizat penyembuhan”, baik di luar maupun di dalam Gereja, semakin meluas dan cenderung mengaburkan iman. Atas situasi ini, Gereja harus mencari cara untuk menyelidiki lebih mendalam hakekat mukjizat penyembuhan , terutama untuk mencegah orang dari kesesatan.